PERAN JAMINAN OBLIGASI SEBAGAI VARIABEL MODERASI TERHADAP PENGARUH RISIKO KREDIT TERHADAP PERINGKAT OBLIGASI PADA BADAN USAHA MILIK DAERAH (BUMD) SEKTOR PERBANKAN DI INDONESIA - Bangun Putra Prasetya; Ananda Setiawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The Risk Profile, which contains credit risk is a factor that influences the BUMD Regional Development Bank's bond rating, so guarantees are needed to convince investors to get involved in buying and selling the BUMD BPD bonds. The purpose of this study is to analyze whether collateral is able to moderate credit risk (Non Performing Loan/ NPL) on bond ratings. In this study, 19 samples from BUMD BPD throughout Indonesia have issued bonds that have a rating at PEFINDO. The results of this study indicate that guarantees are not able to moderate the effect of Non Performing Loan (NPL) on bond ratings. This is due to problems related to the transfer of assets which are constrained by law and bureaucratic technical matters